Legal Review of Transitional Principles (Lex favor reo) in the Criminal Code - Fauzan Safri Hummam; Khalid (Warmadewa Press, 2024)
Changes in criminal law through the recodification process have resulted in the National Criminal Code. One of the main differences with the Wetboek van Strafrecht Criminal Code (WvS The application of the lex favor reo principle is connected to the Criminal Code. The National Criminal Code's Article 3's lex favor reo principle, which is applied as part of criminal law reform, is conceptually intended to safeguard all Indonesian citizens. In order to investigate legal ideas connected to the lex favor reo principle, this study employs normative juridical research using a conceptual approach. According to the study's findings, Article 3 of the National Criminal Code verifies that any modifications to the law made after a criminal conduct has been committed but before the verdict is handed down, then the provisions that are most favorable to the defendant must be applied. This arrangement is a concrete form of the lex favor reo principle, which aims to provide legal certainty and justice for the defendant.